Analisis Pengendalian Mutu Kadar Air Teh Hitam pada Industri Pengolahan Teh - Gustiarini Rika Putri; Rizki Fadhillah Lubis; Asri Yenita (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2021)
Quality control is intended to maintain and improve quality and maintain the safety of the products produced. This study uses Statistical Process Control by using several tools such as check sheets, control charts and fishbone diagrams to determine the cause of the decline in quality in tea with the aim that the next process can minimize the level of product quality decline. This study aims to determine the dominant cause of the decline in tea quality when viewed from the water content in tea. Based on the results of the study, it can be seen that the dominant cause of the decline in tea quality is the highwater content of dry tea. This type of deterioration can be caused by human error and other factors such as machine condition, raw materials and process monitoring.